PENERAPAN MODEL KOOPERATIF TIPE JIGSAW DENGAN BANTUAN MEDIA KARTU SOAL PADA PEMBELAJARAN STATISTIKA - Meifi Anjelina Rumenta; Selfie L. Kumesan; James U.L. Mangobi (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the teacher when practicing the jigsaw type cooperative model with the help of question cards (karsol) media in statistics learning at SMP Negeri 1 Tabukan, South Tengah. This learning model aims for a study plan involving students collaborating to achieve the mission and concurrently organize a group of experts who are taken from each initial group and are expected to become experts in the material they carry, then return to the initial group to teach the expert material to their group mates. In the translation of the data, the author uses the t-test. from the results of the translation of experimental data with n = 10, it is obtained that t_count = 10.38268, and t table = 1.81246 for = 0.05. Because t_hitung = 10.38268 > t_table = 1.81246, it is concluded that the average student learning outcomes by applying the jigsaw type cooperative model with the help of question card media are higher than the KKM value set at SMP Negeri 1 Tabukan, South Tengah. So the use of this learning model has a positive influence, namely, it can improve student learning outcomes.